OPTIMASI AERODINAMIKA BODI MOBIL HEMAT ENERGI KEN DEDES ELECTRIC EVO 3 MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMICS (CFD) - Fakhruddin, Muhammad; Wicaksono, Hangga; Baananto, Fauzan; Firmansyah, Hilmi Iman; Sari, Nurlia Pramita; Muzaki, Mochamad; Akbarsyah D, Khelvindra Rizky; Hardyanto, Noveri Dwi (Eksergi, 2021)
Aerodynamics is a branch of science that discusses the movement of an object in the air. Aerodynamics comes from the words aero = air and dynamics = force of motion. The study of air forces is a branch of fluid mechanics. This study is a continuation of the study of hydrodynamics, where the science of the motion of air has a close relationship with other sciences. Physics, mathematics, mechanics, meteorology and others are branches of science that are closely related to aerodynamics. Where in the science of aerodynamics, it discusses the principle of stationary air, specifically about the changes experienced by the air when there is a change in geometry. In this study, CFD analysis was carried out to inspect and optimize the airflow through the energy-efficient car body "Ken dedes Evo 3" Malang State Polytechnic to participate in energy-efficient car competitions by following the regulations and packaging requirements in energy-efficient car contests. The aerodynamic analysis of the energy-efficient car was carried out using the ANSYS simulation software. This aerodynamic research aims to reduce the drag coefficient and lift coefficient of energy-efficient cars. In the end, the energy-efficient car Ken Dedes Electric Evo 3 has an improved drag coefficient of 0.03 and a lift coefficient of 0.034. This is obtained from the simulation only on the car body.